Different Sex-Based Responses of Gut Microbiota During the Development of Hepatocellular Carcinoma in Liver-Specific Tsc1-Knockout Mice - Huang, Rong; Li, Ting; Ni, Jiajia; Bai, Xiaochun; Gao, Yi; Li, Yang; Zhang, Peng; Gong, Yan (Frontiers in Microbiology, 2018)
Gut microbial dysbiosis is correlated with the development of hepatocellular carcinoma (HCC). Therefore, analyzing the changing patterns in gut microbiota during HCC development, especially before HCC occurrence, is essential for the diagnosis and prevention of HCC based on gut microbial composition. However, these changing patterns in HCC are poorly understood, especially considering the sex differences in HCC incidence and mortality. Here, with an aim to determine the relationship between gut microbiota and HCC development in both sexes, and to screen potential microbial biomarkers for HCC diagnosis, we studied the changing patterns in the gut microbiota from mice of both sexes with liver-specific knockout of Tsc1 (LTsc1KO) that spontaneously developed HCC by 9–10 months of age and compared them to the patterns observed in their wide-type Tsc1fl/fl cohorts using high-throughput sequencing. Using the LTsc1KO model, we were able to successfully exclude the continuing influence of diet on the gut microbiota. Based on gut microbial composition, the female LTsc1KO mice exhibited gut microbial disorder earlier than male LTsc1KO mice during the development of HCC. Our findings also indicated that the decrease in the relative abundance of anaerobic bacteria and the increase in the relative abundance of facultative anaerobic bacteria can be used as risk indexes of female HCC, but would be invalid for male HCC. Most of the changes in the gut bacteria were different between female and male LTsc1KO mice. In particular, the increased abundances of Allobaculum, Erysipelotrichaceae, Neisseriaceae, Sutterella, Burkholderiales, and Prevotella species have potential for use as risk indicators of female HCC, and the increased abundances of Parapervotella, Paraprevotellaceae, and Prevotella can probably be applied as risk indicators of male HCC. These relationships between the gut microbiota and HCC discovered in the present study may serve as a platform for the identification of potential targets for the diagnosis and prevention of HCC in the future.